2018
DOI: 10.1002/lary.27686
|View full text |Cite
|
Sign up to set email alerts
|

Type I thyroplasty: A safe outpatient procedure

Abstract: Objectives/Hypothesis: Overnight hospitalization is routinely advocated following type I thyroplasty (TP) because of concerns for airway compromise. Hospitalization increases cost and patient inconvenience, and may not necessarily be appropriate. This study evaluated complications following surgery and identified predictors for same to assess which patients benefit most from hospitalization.Study Design: Retrospective chart review.Methods: A study was conducted on patients who underwent TP with or without aryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 39 publications
2
38
0
Order By: Relevance
“…The only complications of nonobstructive hematoma and implant extrusion occurred in patients on anticoagulation and in patients with poor implant placement or prior radiation therapy, respectively. 13,15 In our series, there was a one case of implant extrusion due to persistent infection and granulation tissue deposition at the site of primary surgery.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The only complications of nonobstructive hematoma and implant extrusion occurred in patients on anticoagulation and in patients with poor implant placement or prior radiation therapy, respectively. 13,15 In our series, there was a one case of implant extrusion due to persistent infection and granulation tissue deposition at the site of primary surgery.…”
Section: Discussionmentioning
confidence: 73%
“…The reported complication rate for patients undergoing type 1 thyroplasty is between 7% and 20%. 12,13,15,17,18,[19][20][21][22] However, our study found a major complication rate of 5.6% with no long-term morbidity or mortalities. There were 4 cases of airway complications that were considered major; however, none of the patients required intubation or tracheostomy.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, surgical practices often vary by provider and institution. For instance, in an institutional sample of 100 patients undergoing type I thyroplasty reported by Julapan et al, 19 patients received a surgical Penrose drain and 80 patients did not 2 . In contrast, all of the patients at our institution received a surgical drain after type I thyroplasty from 2014 to 2019.…”
Section: Introductionmentioning
confidence: 76%
“…Glottic insufficiency is characterized by incomplete closure of the true vocal cords during phonation, leading to symptoms of dysphonia, vocal fatigue, and occasionally dysphagia or aspiration 1 . Type I thyroplasty has long been considered the gold standard for long‐term surgical management of glottic insufficiency 2,3 . It involves medialization of the true vocal cord with an alloplastic implant 4 .…”
Section: Introductionmentioning
confidence: 99%